PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP MINAT PEMBELIAN ULANG YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA PENGGUNA APLIKASI MAXIM DI BANDA ACEH - Hafiz Arief Virulian; Syarifah Evi Zuhra (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to examine the effect of Price and Service Quality on Repurchase Interest mediated by Customer Satisfaction on Maxim application users in Banda Aceh. The sampling method in this study used purposive sampling with 105 respondents. Methods of Analysis using Path Analysis method or Path Analysis to determine the effect of all the variables involved. The results showed that Price and Service Quality had a positive and significant effect on Repurchase Interest and Customer Satisfaction had a positive and insignificant effect on Repurchase Interest. Furthermore, Customer Satisfaction does not have a partial mediation relationship between Price and Service Quality on Repurchase Interest.